The efficacy of adding topical 5‐fluorouracil to micro‐needling in the treatment of vitiligo: A randomized controlled trial. (31st January 2023) - Pazyar, Nader; Hatami, Mohammad; Yaghoobi, Reza; Parvar, Seyedeh Yasamin; Radmanesh, Mohammad; Hadibarhaghtalab, Maryam
Abstract: Background and Aim: Vitiligo is an autoimmune skin disorder characterized by circumscribed depigmented macules and patches caused by the loss of functional melanocytes. Although there is no definitive treatment for vitiligo, several treatment options have been associated with relative satisfactory outcomes. The purpose of this study was to compare the efficacy of micro‐needling in conjunction with topical 5‐fluorouracil (5‐FU) versus topical tacrolimus ointment in treating vitiligo patches. Patients and Methods: This study included nineteen participants, each of whom received both treatments on two randomly selected vitiligo patches of approximately the same size and location. On one patch, a combination of weekly micro‐needling and topical application of 5‐FU solution was used every other day, while on the other, 0.1% tacrolimus topical ointment was applied twice daily. The G‐score was used to compare treatment outcomes after 3 months. Results: The median duration of the disease in our population was 7 years. Six patients (32%) in the micro‐needling plus topical 5‐FU treated group showed a moderate to excellent response, indicating a significant improvement between both treatments ( p ‐value = 0.019). In contrast, all other patches treated with topical tacrolimus showed poor improvement. Lower extremity and trunk responded more to treatment with micro‐needling plus topical 5‐FU than upper extremity and acral areas. Moreover, none of those who have had the disease for more than ten years have responded to treatment. Mild erythema, pinpoint bleeding, and irritation were detected only in the micro‐needling treated group. Conclusion: The current study showed that using micro‐needling in conjunction with 5‐FU could treat vitiligo patients more efficiently than tacrolimus monotherapy. Despite showing moderate to excellent improvement in patches treated with micro‐needling and 5‐FU, this well‐tolerated office‐based modality still requires additional research.